A study on prevalence of dry eye among postmenopausal women attending ophthalmology OPD - Zoha Arnib; Anand G. Gannur; Z.A. Golewale; Madhu A. Gannur; Vybhavi P. Kaushik (Al Ameen Medical College, 2023)
Purpose: Having insufficient lubrication and moisture on the surface of the eye causes dry eye syndrome. Burning, itchy, weary, red, gritty, and dry eyes are all signs of dry eye syndrome. There are other symptoms such as blurred vision and fatigued eyes. The study's goals and objectives were to find out how common dry eye syndrome is in post-menopausal women at a tertiary care facility in Vijaypura and to analyze sociodemographic characteristics that may be associated with the condition in the group under study. Aims and objectives were to determine the prevalence of dry eye syndrome among post-menopausal women at tertiary care center, Vijaypura and to assess the socio demographic factors related to dry eye syndrome among study population. Method: A cross sectional study was conducted from June 2021 to November 2021 among postmenopausal women attending ophthalmology OPD, 120 patients were evaluated. Patients data was recorded and OSDI scoring was done, visual acuity testing and anterior segment evaluation was done with slit lamp biomicroscopy. Dry eye evaluation was done with schirmers and TBUT testing was done. Results: Prevalence of dry eye among post menopausal women was 47.5%. The prevalence of dry eye was 75% in age group more than 70yrs and 25% in age group (50-55yrs). The schimers test showed majority 29.166% had mild dry eye, 18.33% had moderate dry eye. The prevalence of dry eye with outdoor occupation was 66.66% compared to indoor (33%). Prevalence of dry eye with symptoms was 87.5% and prevalence of dry eye without symptoms was 25%. Conclusion: There is high prevalence of dry eye in postmenopausal women. Patients without symptoms have subclinical dry eye. Patients with outdoor occupation have higher prevalence. It would be advisable to screen all postmenopausal women for dry eye using simple tests. Hence treatment should be initiated early. Schirmers test revealed most patients had mild to moderate dry eye.